Polyelectrolyte composite material and carbon sequestration and channeling prevention application thereof

Through the electrostatic interaction of polyelectrolyte composite materials, the problem of CO2 escape in CO2-EOR is solved, and efficient CO2 carbon sequestration and gas disconnection control during oil flooding is achieved, reducing costs and improving carbon sequestration efficiency.

CN119119591APending Publication Date: 2024-12-13SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411235358.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the existing CO2-EOR technology, the low viscosity and reservoir heterogeneity of CO2 lead to CO2 escape, resulting in low oil displacement efficiency and high cost, making it difficult for traditional gel materials to regenerate and control.

Method used

Using polyelectrolyte composite materials based on electrostatic interactions, the CO2-responsive viscosity-enhancing material composed of sodium carboxymethylcellulose and branched polyethyleneimine is formed by CO2 stimulation to form a polyelectrolyte composite gel to improve viscosity and achieve CO2 blockade.

Benefits of technology

It significantly improves the carbon sequestration efficiency and storage rate of CO2, reduces costs, and effectively controls gas bleeding during the CO2-EOR process, and improves oil displacement efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119591A_ABST
    Figure CN119119591A_ABST
Patent Text Reader

Abstract

The invention discloses a polyelectrolyte composite material and carbon sequestration and channeling prevention application thereof. The polyelectrolyte composite material is a CO2 stimulation tackifying composition based on electrostatic interaction, and is composed of sodium carboxymethyl cellulose (CMC-Na, A), branched polyethyleneimine (PEI, B) and water. The branched polyethyleneimine molecule contains three nitrogen-containing groups, namely primary amino, secondary amino and tertiary amino, after CO2 is dissolved in water, carbonic acid is formed, so that the three amino groups are protonated, and the positively charged cationic ammonium salt is formed. Free carboxyl on the sodium carboxymethyl cellulose is negatively charged and can form a three-dimensional cross-linked network with the cationic branched polyethyleneimine through electrostatic attraction, and macroscopically, the viscosity of the system is increased. In the CO2 geological storage process, the viscosity of the polyelectrolyte composite material is increased, so that CO2 fluid channeling can be effectively blocked, and the CO2 storage rate is increased. Meanwhile, rich amino groups of polyethyleneimine in the system can react with CO2, so that the carbon sequestration rate is further increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of CO2 storage materials, and in particular relates to a carbon fixation application of a CO2 responsive viscosity increasing material. Background Art

[0002] CO2 capture, utilization and storage (CCUS) is a key measure to achieve carbon emission reduction. CO2 storage or storage refers to the long-term fixation or conversion of captured CO2 through physical, chemical and biological methods so that it will not be released into the atmosphere again. The current carbon fixation methods are mainly concentrated in three methods: physical storage, chemical catalysis and biological fixation. Among them, chemical catalysis and biological fixation are still in the research stage, and physical storage technology is relatively mature and is an important strategy to solve the problem of carbon emissions.

[0003] According to the storage environment, physical storage can be divided into geological storage and marine storage. Geological storage is currently the most traditional CO2 landfill technology. This method mainly uses pipeline technology to inject high-concentration CO2 into geological structures, such as oil fields, natural gas reservoirs, and unrecoverable coal seams, and uses the air tightness of geological structures to store CO2 for a long time. It can be divided into technologies such as CO2 enhanced oil recovery (CO2-EOR), CO2 enhanced coalbed methane recovery (CO2-ECBMR), and CO2 enhanced aquifer heat recovery (CO2-EATER). As an important oil recovery method in tertiary oil recovery, CO2-EOR is currently an important way to utilize CO2.

[0004] CO2 leakage (i.e., "gas leakage") caused by the low viscosity of CO2 and the heterogeneity of the reservoir hinders the development of CO2-EOR. At present, polymer gel materials have shown application potential in the control of gas leakage in CO2 oil recovery and storage, but the pumping pressure required for prefabricated gels in the past was too high, and in-situ cross-linking in deep formations was difficult to control. At the same time, fossil-based gel materials are difficult to regenerate and have high costs. Therefore, it is necessary to develop greener and more economical carbon-fixing materials that have low viscosity and are easy to pump on the ground, and high viscosity and can be plugged underground, so as to achieve in-situ controllable CO2 leakage prevention and carbon fixation.

[0005] CO2-stimulated viscosity-increasing materials have been applied in fields such as oilfield fracturing operations, and most research has focused on the viscosity-increasing ability of the materials. However, there are few reports on their ability to fix CO2 in reservoirs and prevent cross-talk during oil displacement. Summary of the invention

[0006] The purpose of the present invention is to address the deficiencies of the prior art and provide a polyelectrolyte composite material and its carbon fixation and anti-channeling applications, introduce CO2 chemical reactions into traditional geological storage, make it more difficult for CO2 to escape from the formation, and achieve carbon fixation.

[0007] The polyelectrolyte composite material provided by the present invention is a CO2-stimulated viscosity-increasing composition based on electrostatic interaction, and is composed of sodium carboxymethylcellulose (CMC-Na, A), branched polyethyleneimine (PEI, B) and water;

[0008]

[0009] In order to ensure good solubility, the mass concentration of sodium carboxymethyl cellulose is in the range of 0 to 2.0%, and not 0%; the mass concentration of branched polyethyleneimine is in the range of 0 to (0.239C CMC-Na —0.020)%, and not 0%.

[0010] Furthermore, the viscosity average molecular weight of the sodium carboxymethyl cellulose is preferably 780,000, and the weight average molecular weight of the branched polyethyleneimine is preferably 1,800.

[0011] The mixture of the composition increases viscosity under CO2 stimulation (after CO2 is introduced) to form a polyelectrolyte complex gel.

[0012] The present invention provides the application of the above-mentioned polyelectrolyte composite material in the field of carbon fixation and / or anti-channeling, and further in the application of CO2 utilization and / or storage (geological storage), and / or gas channeling control in the CO2 oil recovery process (CO2-EOR).

[0013] The present invention also provides a combined application of sodium carboxymethyl cellulose (CMC-Na, A) and branched polyethyleneimine (PEI, B) in the fields of carbon fixation and channeling prevention. The carbon fixation refers to CO2 utilization and / or storage, and the channeling prevention refers to gas channeling control in the CO2 oil recovery process (CO2-EOR).

[0014] The present invention also provides a combined application of sodium carboxymethyl cellulose and branched polyethyleneimine in the absorption and storage of CO2, that is, CO2 is fixed by the absorption of CO2 by branched polyethyleneimine and the blocking of CO2 by gel after viscosity increase under electrostatic action.

[0015] In CO2 storage, the PEI of the present invention, after reacting with CO2 and water, forms a cationic polyelectrolyte through protonation, and then forms a polyelectrolyte complex with an anionic polyelectrolyte sodium carboxymethyl cellulose through electrostatic interaction, which is manifested in the increase of viscosity and the formation of gel on a macro scale. The solvent (water) absorption, the reaction of PEI and CO2, and the final formation of the polyelectrolyte complex gel form a triple effect of capturing CO2, which is expected to greatly increase the amount of CO2 fixed; at the same time, the system is simple to prepare and easy to increase viscosity or gel, so it has great application prospects in related fields such as carbon sequestration and anti-channeling in CCUS.

[0016] The method for preparing the polyelectrolyte complex material comprises the following steps:

[0017] A certain amount of sodium carboxymethyl cellulose is added to a beaker filled with ultrapure water and mechanically stirred until the sodium carboxymethyl cellulose is completely dissolved in the solution; then a certain amount of branched polyethyleneimine solution is added to the sodium carboxymethyl cellulose solution and stirred at the same speed until a uniform solution is formed.

[0018] In the above method, further, in order to ensure good solubility, the viscosity average molecular weight of sodium carboxymethyl cellulose is preferably 780,000 g·mol -1 The mass concentration of sodium carboxymethyl cellulose in the final carbon-fixing material is in the range of 0 to 2.0%, and is not 0%.

[0019] In the above method, further, in order to ensure a good viscosity-increasing effect, the weight average molecular weight of the branched polyethyleneimine is preferably 1,800 g·mol -1 The amount of branched polyethyleneimine solution added is such that the mass concentration of branched polyethyleneimine in the final solution is in the range of 0 to (0.239C CMC-Na —0.020%), and not 0%, of which “0.239C CMC-Na " represents 0.239 times the concentration of sodium carboxymethyl cellulose, and "-" is a minus sign. In the composite material, the critical mass concentration relationship between branched polyethyleneimine and sodium carboxymethyl cellulose (0.239C CMC-Na —0.020%) is controlled by adopting a linear relationship. When the mass concentration of branched polyethyleneimine exceeds the critical concentration relationship, the system will undergo phase separation due to excessive over-crosslinking, resulting in a significant reduction in the viscosity-increasing effect.

[0020] In the above method, further, the reaction is stirred at a rotation speed of 100 rpm using magnetic stirring, and the stirring time is 48 hours.

[0021] The preparation and CO2 response process of the above polyelectrolyte composite material are as follows:

[0022]

[0023] The branched polyethyleneimine molecule contains three nitrogen-containing groups: primary amino group, secondary amino group and tertiary amino group. When CO2 dissolves in water, it forms carbonic acid, which can protonate the three amino groups to form positively charged cationic ammonium salts. The free carboxyl groups on sodium carboxymethyl cellulose are negatively charged and can interact electrostatically with cationic ammonium salts. At this time, the branched polyethyleneimine acts as a "cationic crosslinker" to form a three-dimensional crosslinked network, which is manifested macroscopically as an increase in the viscosity of the system. In the process of CO2 geological storage, the increase in the viscosity of the composite material can effectively block the CO2 cross-flow and increase the CO2 storage rate. At the same time, the rich amine groups of polyethyleneimine in the system can react with CO2, further increasing the carbon fixation rate.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The polyelectrolyte composite material of the present invention can achieve a substantial increase in viscosity and an increase in gel strength in a CO2 environment by utilizing electrostatic attraction. On the one hand, the water in the system will dissolve a portion of CO2; secondly, due to the reaction of PEI and CO2, CO2 can be absorbed in situ underground; finally, due to the increase in viscosity induced by CO2, it is beneficial to seal CO2 in the formation to achieve physical storage. The combination of the two aspects can greatly improve the carbon fixation efficiency, so it has great application potential in the fields of CO2 storage and CO2 in-situ plugging. For example, in the process of CO2 geological storage, the increase in viscosity of the polyelectrolyte composite material can effectively block CO2 crossflow and improve the CO2 storage rate. At the same time, the rich amine groups of polyethyleneimine in the system can react with CO2 to further improve the carbon fixation rate.

[0026] 2. Compared with traditional geological storage technology, the carbon fixation material of the present invention introduces a chemical reaction with CO2, which promotes the carbon fixation effect through chemical reaction. The change in viscosity after the reaction with CO2 is beneficial to its subsequent application. At the same time, the increase in viscosity promotes the CO2 fixation capacity.

[0027] 3. Compared with traditional responsive polymers, the carbon-fixing material of the present invention is composed of a simple compound of only two commercial polymers, has a mature preparation process, a wide range of original sources, and low cost, and has great advantages in both ease of preparation and economy. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The results of the high temperature and high pressure carbon fixation test of the polyelectrolyte composite material (0.9% CMC-Na / 0.15% PEI) (temperature 45°C, sodium chloride concentration 4500 mg·L -1 ).

[0029] Figure 2 The results of the high temperature and high pressure carbon fixation test of the polyelectrolyte composite material (1.3% CMC-Na / 0.05% PEI) (temperature 90°C, sodium chloride concentration 20000 mg·L -1 ).

[0030] Figure 3 The results of underground in-situ carbon fixation test of pure CMC-Na with a mass fraction of 1.3%, pure PEI with a mass fraction of 0.05%, and carbon fixation material (1.3% CMC-Na / 0.05% PEI) (temperature 90°C, sodium chloride concentration 20000 mg·L -1 ).

[0031] Figure 4The CO2 blocking test results of the polyelectrolyte composite material (1.3% CMC-Na / 0.05% PEI) (temperature 90°C, sodium chloride concentration 20000 mg·L -1 ).

[0032] Figure 5 These are the long-term aging stability test results of the polyelectrolyte composite material (1.3% CMC-Na / 0.05% PEI). DETAILED DESCRIPTION

[0033] The present invention is further described below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential improvements and adjustments to the present invention according to the above-mentioned invention content and implement the invention specifically, which still falls within the scope of protection of the invention.

[0034] In the following examples, the sodium carboxymethyl cellulose and branched polyethyleneimine are both commercially available.

[0035] Example 1

[0036] Dissolve 0.9% sodium carboxymethyl cellulose in 4500 mg L -1 The mixture was mechanically stirred at 100 rpm for 48 h in a sodium chloride solution until it was completely dissolved. Then, a branched polyethyleneimine solution with a mass concentration of 10% was added dropwise to a certain amount of sodium carboxymethyl cellulose solution in an amount such that the mass fraction of branched polyethyleneimine in the obtained mixed solution was 0.15%. The mixed solution was stirred at 100 rpm for 10 min until it was completely uniform, thereby obtaining a polyelectrolyte composite material based on electrostatic interaction.

[0037] The high temperature and high pressure carbon fixation test was as follows: the above polyelectrolyte composite material was placed in the kettle of the high temperature and high pressure carbon fixation device, CO2 was stored in the floating piston accumulator, and injected into the kettle using an ISCO syringe pump. During the entire experiment, the temperature was controlled at 45°C and the pressure in the kettle was controlled at 10MPa. The injection rate of CO2 was constant at 0.5mL·min -1 . Use 4500mg·L -1 The sodium chloride solution was used as the control group to conduct the same experiment. The gas volume injected and the gas flow meter reading at the tail end were used to monitor the gas intake and gas production of the kettle in real time. The method for calculating the carbon fixation is as follows:

[0038] Carbon fixation amount = V inlet -V outlet

[0039] Among them, V inlet Indicates the volume of injected CO2, mL; V outletIndicates the volume of CO2 at the outlet, mL.

[0040] Test results:

[0041] like Figure 1 As shown in Figure 2, at 45 °C, the CO2 accumulation in 100 g of the polyelectrolyte composite material is 11.863 g, and the CO2 accumulation in 100 g of sodium chloride brine (mass concentration is 4500 mg·L -1 ) absorbed 5.078 g CO2. It can be calculated that the carbon fixation capacity of 100 g polyelectrolyte composite material increased by 6.785 g compared with 100 g brine.

[0042] Example 2

[0043] Dissolve 1.3% sodium carboxymethyl cellulose in 20000 mg L -1 The mixture was mechanically stirred at 100 rpm for 48 h in a sodium chloride solution until it was completely dissolved. Then, a branched polyethyleneimine solution with a mass concentration of 10% was added dropwise to a certain amount of sodium carboxymethyl cellulose solution in an amount such that the mass fraction of branched polyethyleneimine in the obtained mixed solution was 0.05%. The mixed solution was stirred at 100 rpm for 10 min until it was completely uniform, thereby obtaining a polyelectrolyte composite material based on electrostatic interaction.

[0044] The high temperature and high pressure carbon fixation test is as follows: the above carbon fixation materials are placed in the kettle of the high temperature and high pressure carbon fixation device, CO2 is stored in the floating piston accumulator, and is injected into the kettle using an ISCO syringe pump. During the entire experiment, the temperature is controlled at 90°C and the pressure in the kettle is controlled at 10MPa. The injection rate of CO2 is constant at 0.5mL·min -1 The gas volume injected and the reading of the tail gas flow meter are used to monitor the gas intake and gas production of the kettle in real time. The method for calculating the carbon fixation is as follows:

[0045] Carbon fixation amount = V inlet -V outlet (1)

[0046] Among them, V inlet Indicates the volume of injected CO2, mL; V outlet Indicates the volume of CO2 at the outlet, mL.

[0047] Test results:

[0048] like Figure 2 As shown in Figure 2, at 90 °C, the CO2 accumulation in 100 g of the polyelectrolyte composite material is 6.95 g, and the CO2 accumulation in 100 g of sodium chloride brine (mass concentration is 20000 mg·L -1) absorbs 1.95g CO2, and it can be calculated that the carbon fixation capacity of 100g polyelectrolyte composite material is 5.0g higher than that of 100g brine. Comparing the CO2 absorption capacity at room temperature and pressure and at high temperature and high pressure, the contribution of CO2-induced gelation to carbon fixation is more obvious at high temperature and high pressure, and its net contribution to carbon fixation increases with increasing temperature.

[0049]

[0050] Example 3

[0051] Dissolve 1.3% sodium carboxymethyl cellulose in 20000 mg L -1 The mixture was mechanically stirred at 100 rpm for 48 h in a sodium chloride solution until it was completely dissolved. Then, a branched polyethyleneimine solution with a mass concentration of 10% was added dropwise to a certain amount of sodium carboxymethyl cellulose solution in an amount such that the mass fraction of branched polyethyleneimine in the obtained mixed solution was 0.05%. The mixed solution was stirred at 100 rpm for 10 min until it was completely uniform, thereby obtaining a polyelectrolyte composite material based on electrostatic interaction.

[0052] The simulated underground carbon fixation test was as follows: CO2 and the above-mentioned polyelectrolyte composite were stored in a floating piston accumulator and injected into the core using an ISCO syringe pump. During the entire experiment, the temperature was controlled at 90°C, and the confining pressure and back pressure were controlled at 18 MPa and 10 MPa, respectively. The injection rate of all fluids was constant at 0.5 mL min -1 The gas volume injected and the reading of the tail gas flow meter are used to monitor the gas intake and gas production of the core in real time. The carbon fixation rate is calculated as follows:

[0053]

[0054] Among them, V inlet Indicates the volume of injected CO2, mL; V outlet Indicates the volume of CO2 at the outlet, mL.

[0055] The same experiment as above was carried out using a pure CMC-Na solution with a mass fraction of 1.3% and a pure PEI solution with a mass fraction of 0.05% as a control group.

[0056] Test results:

[0057] like Figure 3As shown in the figure, for the polyelectrolyte composite material, in the front CO2 plug, when CO2 has not yet broken through, no CO2 is discharged from the core outlet, so the carbon fixation rate is 100%. After CO2 breakthrough occurs, the outlet gas volume gradually increases, resulting in a gradual decrease in the carbon fixation rate. In the polymer plug, since the viscosity of the carbon fixation material is greater than that of CO2, part of the CO2 retained in the core during the injection process will be displaced, resulting in the gas flow rate detected by the gas flow meter at the outlet, so the carbon fixation rate will decrease to a certain extent at this time. In the subsequent protective CO2 plug and the post-CO2 plug, since the viscosity-enhanced carbon fixation material blocks the core to a certain extent, it is more difficult for CO2 to break through, which means that the gas flow rate at the outlet is small, a large amount of CO2 is "bound" in the core, and the carbon fixation rate is correspondingly increased, up to 70.0%.

[0058] like Figure 3 As shown, for pure CMC-Na solution, since CMC-Na itself has a certain viscosity, the carbon fixation rate also increases accordingly before CO2 breaks through. However, gas breakthrough occurs in a short time, resulting in a decrease in the carbon fixation rate, and the final carbon fixation rate is 49.5% (54.1% after calculating the compensation value). Compared with the polyelectrolyte composite material, its carbon fixation rate decreases by 15.9%, thus proving the fixation effect of the polyelectrolyte composite material on CO2. For pure PEI solution, in the protective CO2 plug and the post-CO2 plug, since PEI has a certain chemical absorption effect on CO2, the carbon fixation rate also increases accordingly before CO2 breaks through. However, gas breakthrough occurs in a short time, resulting in a decrease in the carbon fixation rate, and the final carbon fixation rate is 52.2% (63.3% after calculating the compensation value). Compared with the polyelectrolyte composite material, its carbon fixation rate decreases by 6.7%, proving the fixation effect of the polyelectrolyte composite material on CO2.

[0059] like Figure 4 As shown, for the polyelectrolyte composite material, due to its CO2-stimulated viscosity-increasing effect, the CO2 breakthrough pressure is significantly improved, and the blocking rate is 83.3%, indicating that the polyelectrolyte composite material can effectively alleviate the gas channeling problem while fixing CO2 in situ.

[0060] Example 4

[0061] Dissolve 1.3% sodium carboxymethyl cellulose in 20000 mg L -1The mixture was mechanically stirred at 100 rpm for 48 h in a sodium chloride solution until it was completely dissolved. Then, a branched polyethyleneimine solution with a mass concentration of 10% was added dropwise to a certain amount of sodium carboxymethyl cellulose solution in an amount such that the mass fraction of branched polyethyleneimine in the obtained mixed solution was 0.05%. The mixed solution was stirred at 100 rpm for 10 min until it was completely uniform, thereby obtaining a polyelectrolyte composite material based on electrostatic interaction.

[0062] The high temperature aging stability test is as follows: CO2 is blown into the above carbon-fixing material and placed in a pressure-resistant glass tube, placed in a vacuum drying oven at 90°C for aging, and samples are taken at regular intervals for viscosity testing using a rotational rheometer.

[0063] Test results:

[0064] like Figure 5 As shown in the figure, at 90°C, the viscosity before aging is 330 mPa·s, and the viscosity after aging for 30 days is 214 mPa·s. The viscosity retention rate after aging for 30 days is 65.1%, indicating that the polyelectrolyte composite material has good long-term aging stability.

Claims

1. A polyelectrolyte complex material, characterized in that: The composite material is a CO2-stimulated viscosity-increasing composition based on electrostatic interaction, and is composed of sodium carboxymethyl cellulose, branched polyethyleneimine and water; The mass concentration of sodium carboxymethyl cellulose is in the range of 0 to 2.0% and is not 0%; the mass concentration of branched polyethyleneimine is in the range of 0 to (0.239C CMC-Na —0.020)%, and not 0%.

2. Application of the polyelectrolyte complex material according to claim 1 in the field of carbon fixation and / or anti-channeling.

3. Application of the polyelectrolyte composite material according to claim 1 in CO2 utilization and / or storage, and / or gas cross-talk control in CO2 oil recovery process.

4. The use of the polyelectrolyte complex material according to claim 1 in the absorption and storage of CO2, that is, fixing CO2 by absorbing CO2 through branched polyethyleneimine and blocking CO2 through gel after viscosity increase under electrostatic action.

5. Combined application of sodium carboxymethyl cellulose and branched polyethyleneimine in the field of carbon fixation and / or anti-channeling.

6. Combined application of sodium carboxymethyl cellulose and branched polyethyleneimine in CO2 utilization and / or storage, and / or gas cross-talk control in CO2 oil recovery process.

7. The combined application of sodium carboxymethyl cellulose and branched polyethyleneimine in the absorption and storage of CO2, that is, the CO2 is fixed by the absorption of CO2 by branched polyethyleneimine and the blocking of CO2 by the gel after viscosity increase under electrostatic action.